2019
DOI: 10.1016/j.ajo.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Ocular Features of Pediatric Myasthenias

Abstract: Purpose: To report the incidence, demographics, and ocular findings of children with myasthenia Design: Retrospective cohort study Methods: The medical records of all children (< 19 years) examined at Mayo Clinic with any form of myasthenia from January 1 1966, through December 31, 2015, were retrospectively reviewed.Results: A total of 364 children were evaluated during the study period, of which 6 children were residents of the Olmsted County at the time of their diagnosis, yielding an annual age-and sex-adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…In a long-term follow-up study in Denmark from 1996-2009, the incidence rate was 7 times higher in those aged 10–19 years compared to those aged 0–9 years (2.2/million v 0.3/million person-years) ( 3 ). The incidence in Olmstead county, USA, was determined as part of a larger cohort study as 1.2/million person years but this was only based on two confirmed cases ( 4 ). In contrast to these studies, a national study of AChR antibody positive MG from South Africa, estimated to account for 75% of cases, showed a higher incidence rate of 4.3/million person-years in those under 20 years ( 5 ).…”
Section: Epidemiology Of Jmgmentioning
confidence: 99%
“…In a long-term follow-up study in Denmark from 1996-2009, the incidence rate was 7 times higher in those aged 10–19 years compared to those aged 0–9 years (2.2/million v 0.3/million person-years) ( 3 ). The incidence in Olmstead county, USA, was determined as part of a larger cohort study as 1.2/million person years but this was only based on two confirmed cases ( 4 ). In contrast to these studies, a national study of AChR antibody positive MG from South Africa, estimated to account for 75% of cases, showed a higher incidence rate of 4.3/million person-years in those under 20 years ( 5 ).…”
Section: Epidemiology Of Jmgmentioning
confidence: 99%
“…A review from Thailand, but in juveniles (<15 years) presenting with ocular MG, also found limitations of EOM movement in more than 50% (of 62), and most had complete duction failure ( 29 ). Juvenile MG cases seen at the Mayo clinic (most were Caucasian children) found limitations of EOM movement in 30%, although there may be a bias to more severe cases in this cohort as most patients were not residents of the county ( 19 ).…”
Section: Resultsmentioning
confidence: 85%
“…A study from China found similar proportions of AChR-Abs by RIA and cell-based assay (CBA) in juveniles (<19 years of age) compared to adult-onset MG cases, although 18% of the juveniles (compared to 10% of adults) were only positive by CBA ( 31 ). The age-adjusted incidence rates of AChR-Ab positive MG among juveniles from South Africa ( 24 ) appeared to be higher than in Caucasian cohorts from the UK, USA, Norway, and Canada (≈3 per million vs. <1.5 per million, respectively) ( 12 , 19 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Insiden di daerah Olmstead Amerika Serikat, pada studi kohort yang lebih besar menunjukkan 1,2 juta orang per tahun tetapi hanya didasarkan pada 2 kasus yang dikonfirmasi (Mansukhani et al, 2019). Berbeda dengan studi ini, studi di Afrika Selatan dengan kasus antibodi AChR miastenia gravis positif diperkirakan mencakup 75% kasus, menunjukkan tingkat insiden yang lebih tinggi yaitu sebesar 4,3 juta orang per tahun pada mereka yang berusia di bawah 20 tahun (Mombaur et al, 2015).…”
Section: Epidemiologi Miastenia Gravis Juvenilunclassified